MENGUKUR ADOPSI FINTECH UNTUK MENDUKUNG USAHA BAGI MITRA PELAKU UMKM BINAAN YAYASAN PALMA SEJAHTERA DI JAKARTA - Indriyarti, Eko Retno; Leon, Farah Margaretha; Purba, Yosephina; Murdiah, Siti; Liberty, Batara Alexander (Jurnal Pengabdian dan Kewirausahaan, 2022)
One of the problems that often occur in micro, small and medium enterprises (MSMEs) in Indonesia is capital. Moreover, during the COVID-19 pandemic, where the limitations of running a business and the limitations of community mobility are unavoidable obstacles that cause business turnover to be hampered. During this problem, an opportunity arose from the development of financial technology (fintech) which offers various solutions, one of which is online financing for businesses. This aims to support existing businesses ranging from capital to operations and business marketing. This is the background for the implementing team for community service activities from the Faculty of Economics and Business, Trisakti University to provide counseling to MSME actors to increase knowledge of this form of fintech. This activity took place on December 20, 2021, by providing counseling to 25 MSME actors assisted by the Palma Sejahtera Foundation located in Palmerah, West Jakarta. From the activity carried out, participants felt that the material provided was interesting, the material was easy to understand, and the material provided could increase knowledge and abilities. The participants also considered that the appointed resource persons had competence with the material presented and could convey the material. Overall, the participants were satisfied with the implementation of this community service activity. In addition, from a brief measurement carried out, MSME actors in these fostered partners still depend on security factors to be able to adopt the fintech platform. In addition, participants are also still dependent on a series of perceived ease-of-use factors for the fintech platform.